Human and Social Values Included in EFL Curricula for Basic Stage in Jordan - Sahm Tayseer Al-Ma'aitah (Matondang Journal, 2022)
The study aims to indicate the most important human and social relations values included in the English language curricula for the basic stage in Jordan. To achieve the study objectives, the researcher prepared a checklist consisting of (17) values. The results indicate that there are (2744) human and social relations values in the English language textbooks of the basic stage in Jordan. This is due to the fact that textbooks encourage communication with others, in addition to the adaptation and integration with them, which is the goal of the educational process. Also, the textbooks of the 6th grade contained the highest repetition of Human and Social Relations values, while the textbooks of the 2nd grade contained the lowest repetition of the same values.